Characteristic and Performance Tests of Membrane PES in Biodiesel Purification by using Ultrafiltration Process - Sri Mulyati; Fachrul Razi; . Zuhra; Erna Oktari; . Syawaliah (Syiah Kuala University, 2015)
Polyethersulfone (PES) membranes were prepared via phase inversion method. The effect of polymer concentration on the morphology of the fabricated membranes were studied. Furthermore, the effect of transmembrane pressure (TMP)was also studied on the filtration performance of biodiesel purification. The morphology of fabricated PES membrane was analyzed by using Scanning Electron Microscopy (SEM) indicated that the PES membranes had skin layer on the membrane surface and pores layer on the bottom surface. The permeability coefficient (Lp) of PES membranes were about 21-40 L/m2.h. The Molecular Weight Cut Off (MWCO) test shows that the rejection of dextran solution with the molecular weight 18,8Kda was above 90%. The water contact angle of PES membranes was measured to know the hydrophilicity of PES membrane. The water contact angle was about 73oconfirmed that the PES membrane was hydrophobic. The increasing ofTrans-membrane Pressure (TMP) had a significant effect on the permeability of membrane which isthe permeability of biodiesel increases by increasing the TMP. The maximum of flux was obtained about 110 ml/sec